2018
DOI: 10.1126/sciadv.aaq1543
|View full text |Cite
|
Sign up to set email alerts
|

Probing quantum coherence in single-atom electron spin resonance

Abstract: Phase coherence of single-atom spins on surfaces is investigated in a scanning tunneling microscopy experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
182
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(209 citation statements)
references
References 50 publications
22
182
4
1
Order By: Relevance
“…This nonlinear process is enhanced near the resonance condition and depends on the square of the driving amplitude, which is compatible with Ref. [19]. The effect is based on a current-induced spin-torque and does not assume any effective time dependence of the local moment Hamiltonian.…”
Section: Discussionsupporting
confidence: 83%
“…This nonlinear process is enhanced near the resonance condition and depends on the square of the driving amplitude, which is compatible with Ref. [19]. The effect is based on a current-induced spin-torque and does not assume any effective time dependence of the local moment Hamiltonian.…”
Section: Discussionsupporting
confidence: 83%
“…We find a zero-RF drive Γ of (2.5 ± 0.2) mT and a corresponding coherence time of 2 * of (4.5 ± 0.4) ns. This represents a lower bound for the intrinsic T2 because additional broadening mechanisms related to the vibrational stability of the tip [7], magnetic fluctuations [23], and decoherence by tunneling electrons [23] have not been accounted for.…”
Section: B Esr Demonstrationmentioning
confidence: 99%
“…Berggren and Fransson [13] proposed that the spin polarization of the electrodes generates a finite time dependence of the uniaxial and transverse anisotropy with the ac signal. They showed that this change leads to a finite ESR signal in integer spin systems, and they predicted a dependence of the ESR frequency on the tip-sample distance, a shift that has not been observed in recent experiments [4] when changing the current by a factor of 30.…”
Section: Introductionmentioning
confidence: 88%
“…The demonstration of reproducible single-atom [1] and single-molecule [2,3] electron spin resonance (ESR) has opened in the analysis of surface science at the atomic scale. Conserving the atomic spatial resolution of the scanning tunneling microscopy (STM), STM-ESR provides unprecedented energy resolution in the neV energy scale [4]. Moreover, it can be combined with high time resolution pump-and-probe techniques [5,6].…”
Section: Introductionmentioning
confidence: 99%